Development of a new type of multifunctional fucoidan-based nanoparticles for anticancer drug delivery. (1st June 2017) - Lu, Kun-Ying; Li, Rou; Hsu, Chun-Hua; Lin, Cheng-Wei; Chou, Shen-Chieh; Tsai, Min-Lang; Mi, Fwu-Long
Highlights: Development of a novel mutli-stimuli-responsive fucoidan/protamine nanoparticle. P-selectin targeting, charge conversion, and stimuli-responsive properties. Drug release was triggred by enzymatic digestion and acidic intracellular pH. DOX-loaded nanoparticles improved inhibitory effect against MDA-MB-468 cancer cells. Abstract: Fucoidan, a sulfated marine polysaccharide, has many potential biological functions, including anticancer activity. Recently, fucoidan has been reported to target P-selectin expressed on metastatic cancer cells. Increasing research attention has been devoted to the developments of fucoidan-based nanomedicine. However, the application of traditional chitosan/fucoidan nanoparticles in anticancer drug delivery may be limited due to the deprotonation of chitosan at a pH greater than 6.5. In this study, a mutli-stimuli-responsive nanoparticle self-assembled by fucoidan and a cationic polypeptide (protamine) was developed, and their pH-/enzyme-responsive properties were characterized by circular dichroism (CD) spectroscopy, dynamic light scattering (DLS), and zeta potential analysis. Enzymatic digestion and acidic intracellular microenvironment (pH 4.5–5.5) in cancer cells triggered the release of an anticancer drug (doxorubicin) from the nanoparticles. The protamine/fucoidan complex nanoparticles with P-selectin mediated endocytosis, charge conversion and stimuli-tunable release properties showed an improved inhibitory effect against a metastatic breast cancer cell line (MDA-MB-231).